Potato Organic Farming in Batu City, Indonesia - Sugiarto Sugiarto; Rudi Sulistiono; Sudiarso Sudiarso; Soemarno Soemarno (The Indonesian Green Technology Journal, 2013)
Organic potato cultivation was an effort to improve declining quality of potato agroecosystems and to  preserve soil fertility. This study was conducted to analyze pattern of farming system and land management on the area of organic potatoes in Batu city. Research was conducted by the survey method, respondents were determined by the method of stratified cluster sampling. Farmer respondents were experienced organic potato farmer and as "expert leaders". Results show that the mindset of farmers were still characterized by limited understanding of "landuse and the environment" (Score = 2). While the availability of raw materials of organic fertilizer in research sites was very limited and insufficient (score = 1). Availability of organic seed potatoes were very limited, and even tend to be scarced (Score = 1). However, in the business area of potatoes, there were the local variety of potato that grows wild and the local farmer named them as  "Crazy Potato". This potato high resistance to environmental stresses, pests, and diseases. Impact of conventional farming to changes in environmental quality (Score = 2) characterized by agro-ecosystems that had been damaged. Soil fertility at this point (Score = 2), including the criteria for "low fertility", meaning the land was considered infertile. Granola varieties of organic potato production average was 11.17 tons/ha, while the Atlantic variety was 12.43 tons/ha. Organic potato farming risk (score = 4), including the level of "high risk of failure". Decrease in the number of predators (Score = 3), reflecting the extinction rate was high (40-59%). Organic potato price stability (Score = 1) were low, and the price was considered unstable. Organic potato price (Score = 3) two times more expensive than conventional potatoes. Quality of the organic potato agroecosystem has suggested symptom of degradation. Improvement of the quality of agroecosystems requires a more stringent public policies that bind all actors in the center of potato farming organically. The sustainable organic farming of potato requires the local government support, the business community and potato farmer in solving any problems. Potato market institutions, farming partnerships and marketing linkages are relatively weak and must be strengthened and empowered. Keywords: potato, organic farming, agro-ecosystem